Seismic system reliability analysis of bridges using the multiplicative dimensional reduction method. Issue 11 (2nd November 2018) - Zhang, Jin; Bi, Kaiming; Zheng, Shixiong; Jia, Hongyu; Zhang, De-Yi
Abstract: A combined method of finite element reliability analysis and multiplicative dimensional reduction method (M-DRM) is proposed for systems reliability analysis of practical bridge structures. The probability distribution function of a structural response is derived based on the maximum entropy principle. To illustrate the accuracy and efficiency of the proposed approach, a simply supported bridge structure is adopted and the failure probability obtained are compared with the Monte Carlo simulation method. The validated method is then applied for the system reliability analysis for a practical high-pier rigid frame railway bridge located at the seismic-prone region. The finite element model of the bridge is developed using OpenSees and the M-DRM method is used to analyse the structural system reliability under earthquake loading.